Does business geographical acting areas impact on intrapreneurship and sustainability strategies? - Duarte, Nelson (2020)
The present paper aims to analyze the positive or negative impact of local integrated firms on strategies of intrapreneurship and sustainability. The study was developed in the region of Tâmega e Sousa, located in the north of Portugal. For that 283 firms from manufacturing and construction industries were analyzed. By local integrated firm were considered those firms that are doing all their business activities within the region where they are established. Most of firms (83.2%) in this region present very good results in the adoption of sustainable strategies, while 80.9% present a weak adoption of intrapreneurship strategies. Crossing variables on local integration and sustainability it was found a light tendency in favor of local firms, i.e., local firms apparently are more concerned with the regional sustainable development, than those that are acting outside the region borders. On what regards the relation between local integration and the adoption of intrapreneurship strategies, those firms that are doing business beyond the region are adopting more intrapreneurship strategies.